Self-healing high-thermal-conductivity silicon-based flame-retardant insulating adhesive film and preparation method thereof

By leveraging the synergistic effect of organosilicon-modified borate esters containing dynamic disulfide bonds, epoxy siloxane-grafted ammonium polyphosphate, and methyl vinyl silicone rubber, a silicon-based flame-retardant insulating adhesive film with high thermal conductivity, flame retardancy, and self-healing properties was prepared. This solved the problems of insufficient thermal conductivity, weak flame retardancy, and insufficient self-healing ability of traditional silicon-based films, thus meeting the thermal management and safety requirements of high-power equipment.

CN120944473APending Publication Date: 2025-11-14RUIHE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511189110.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-25
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Traditional silicon-based adhesive films have insufficient thermal conductivity, weak flame retardancy, and lack self-healing ability, making it difficult to meet the thermal management and safety requirements of high-power equipment.

Method used

A highly thermally conductive, flame-retardant, and self-healing silicone-based flame-retardant insulating adhesive film is formed by using organosilicon-modified borate esters containing dynamic disulfide bonds, epoxy siloxane-grafted ammonium polyphosphate, and methyl vinyl silicone rubber, through physical mixing and chemical crosslinking.

Benefits of technology

It significantly improves the thermal conductivity, self-healing efficiency and flame retardancy of the film, while maintaining good insulation properties, extending the service life of electronic devices and reducing maintenance costs caused by thermal runaway or interface failure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120944473A_ABST
    Figure CN120944473A_ABST
Patent Text Reader

Abstract

The invention discloses a self-healing high-thermal-conductivity silicon-based flame-retardant insulating adhesive film and a preparation method thereof in the field of functional polymer materials. According to the self-healing high-thermal-conductivity silicon-based flame-retardant insulating adhesive film and the preparation method thereof, performance improvement is realized by designing two brand-new modified compounds and optimizing a formula and a process. According to the film, methyl vinyl silicone rubber is used as a basic silicon substrate, organic silicon modified borate containing dynamic disulfide bonds and epoxy siloxane grafted ammonium polyphosphate are added, and fumed silica, spherical boron nitride, magnesium hydroxide and other components are used as auxiliary materials. The preparation method comprises the steps of mixing, dispersing, drying and curing all the raw materials, and the prepared film has the characteristics of high heat conductivity, self-healing, flame retardance and insulation and is suitable for electronic device packaging and other scenes with high requirements for heat management and safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional polymer materials technology, specifically to a self-healing, high thermal conductivity, silicon-based flame-retardant insulating adhesive film and its preparation method. Background Technology

[0002] With the rapid development of 5G communications, new energy vehicles, and flexible electronics, the integration and power density of electronic devices are continuously increasing, leading to ever-growing heat dissipation demands and placing higher requirements on the safety and reliability of materials. While traditional silicon-based adhesive films possess good insulation and flexibility, they are ill-suited for high-power applications. Insufficient thermal conductivity can cause heat buildup, leading to performance degradation or even device failure; weak flame retardancy poses a risk of fire at high temperatures, threatening equipment and operational safety. Furthermore, microcracks caused by thermal stress or mechanical impact during electronic device operation, if unable to self-repair, can further exacerbate interface failures and significantly shorten device lifespan. These bottlenecks constrain the development of electronic devices towards higher stability and longer lifespan.

[0003] The performance defects of traditional silicon-based adhesive films mainly stem from the structural limitations of the materials themselves and the inadequacy of modification methods. In terms of thermal conductivity, the intrinsic thermal conductivity of pure silicon is extremely low. Although this can be improved by filling with high thermal conductivity fillers, the weak interfacial bonding and uneven dispersion of the fillers with the silicon matrix are common problems, resulting in limited improvement in thermal conductivity. Regarding flame retardancy, traditional modifications often rely on halogen-based or phosphorus-based flame retardants. The former releases toxic gases upon combustion, while the latter is prone to migration and loss, making it difficult to meet environmental protection and long-term use requirements. While self-healing functionality can be achieved through microencapsulation technology or dynamic covalent bonds, dynamic bonds have poor stability in the silicon matrix, resulting in a self-healing efficiency typically below 70%, and the repair conditions are stringent, failing to meet the convenience requirements of practical applications.

[0004] To address the aforementioned issues, developing a novel silicon-based adhesive film possessing high thermal conductivity, flame retardancy, insulation, and self-healing properties has become an urgent industry need. This invention overcomes the performance bottlenecks of traditional materials by designing two novel modified compounds: one compound imparts self-healing capability through dynamic disulfide bonds, while introducing borate ester bonds to enhance flame retardancy and combining with a high thermal conductivity filler to strengthen thermal conductivity; the other compound provides a highly efficient flame retardant agent through grafting ammonium polyphosphate and optimizes interfacial bonding to prevent filler agglomeration. The synergistic effect of these two compounds with the basic silicon matrix results in a film that significantly outperforms traditional materials in terms of thermal conductivity, self-healing efficiency, flame retardancy rating, and insulation performance. This film can be widely applied in scenarios with stringent requirements for thermal management and safety performance, such as electronic device packaging and thermal management of new energy batteries. Summary of the Invention

[0005] The purpose of this invention is to provide a self-healing, high thermal conductivity, flame-retardant, insulating adhesive film based on silicon and its preparation method. This invention solves the problems of existing silicon-based adhesive films, such as low thermal conductivity, insufficient flame retardancy, lack of self-healing ability, difficulty in repairing microcracks, and inability to meet the thermal management and safety requirements of high-power equipment.

[0006] The present invention achieves the above objectives through the following technical solutions: A self-healing, high thermal conductivity, silicon-based flame-retardant insulating adhesive film comprising the following parts by weight of raw materials: Methyl vinyl silicone rubber: 90-110 parts by weight; Organosilicon-modified borate ester containing dynamic disulfide bonds: 10-20 parts by weight; Epoxysiloxane-grafted ammonium polyphosphate: 5-15 parts by weight; Fumed silica: 20-30 parts by weight; Magnesium hydroxide: 10-15 parts by weight; Toluene: 50-80 parts by weight; Spherical boron nitride: 40-60 parts by weight; The preparation steps of the organosilicon-modified borate ester containing dynamic disulfide bonds include: A1, adding boric acid to anhydrous ethanol, refluxing to generate triethyl borate, distilling under reduced pressure, adding a siloxane containing disulfide bonds, and reacting with magnetic stirring at 80-82℃ to generate an intermediate; A2, subsequently, dispersing boron nitride nanosheets in N,N-dimethylformamide, sonicating, adding the intermediate, and reacting with a solvothermal agent at 120-122℃, filtering after cooling, washing alternately with N,N-dimethylformamide and ethanol, and vacuum drying at 60-62℃.

[0007] In the preparation of organosilicon-modified borate esters containing dynamic disulfide bonds in this invention, the first step is the esterification reaction of boric acid with anhydrous ethanol: the three hydroxyl groups (-OH) in the boric acid molecule condense with the hydroxyl groups of ethanol under reflux conditions (high temperature promotes dehydration), removing three water molecules to generate triethyl borate, and the three ethoxy groups (-OEt) retained in the molecule provide active sites for subsequent reactions. Subsequently, a siloxane containing disulfide bonds (such as bis(3-mercaptopropyl)tetrasulfide) is added, and the ethoxy groups and the terminal mercapto groups (-SH) of the siloxane undergo a condensation reaction at 80-82°C, removing hydrogen atoms to form Si-O bonds, while the disulfide bonds (-SS-) are retained, thereby constructing an intermediate structure in which organosilicon segments are connected to disulfide bonds via borate ester bonds (-OB(OEt)2-O-). In the second step, boron nitride nanosheets are uniformly suspended in N,N-dimethylformamide after ultrasonic dispersion. The hydroxyl groups (-OH) or oxygen vacancies on their surface undergo hydrolysis and condensation reactions with the ethoxy groups of the intermediate siloxane segments, removing methanol to generate Si-O-Si bonds. This stabilizes the boron nitride nanosheets in the organosilicon network, forming composite particles that have both thermal conductivity and self-healing functions.

[0008] According to a preferred embodiment of the present invention, the methyl vinyl silicone rubber was purchased from Chengdu Sibao Technology Co., Ltd., and the model number is 110-2 (methyl vinyl silicone rubber, vinyl content 0.1%, molecular weight 500,000).

[0009] According to a preferred embodiment of the present invention, the boric acid was purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd., and the product name was boric acid (analytical grade, CAS: 10043-35-3).

[0010] According to a preferred embodiment of the present invention, the anhydrous ethanol was purchased from Tianjin Kemei Chemical Reagent Co., Ltd., and the product is anhydrous ethanol (analytical grade, CAS: 64-17-5).

[0011] According to a preferred embodiment of the present invention, the disulfide-containing siloxane was purchased from Nanjing Shuguang Chemical Group Co., Ltd., and its product name is bis(3-mercaptopropyl)tetrasulfide (Si-69, purity ≥98%).

[0012] According to a preferred embodiment of the present invention, the boron nitride nanosheets were purchased from Xiamen Kaina Graphene Technology Co., Ltd., and the model is KNB-NS (sheet thickness < 50 nm, lateral dimension 5-10 μm).

[0013] According to a preferred embodiment of the present invention, the N,N-dimethylformamide was purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd., and the product name is N,N-dimethylformamide (analytical grade, CAS: 68-12-2).

[0014] According to a preferred embodiment of the present invention, the fumed silica was purchased from Shandong Baichuan New Material Technology Co., Ltd., and the type is H150 (specific surface area 200m²). 2 / g, native particle size 12nm).

[0015] According to a preferred embodiment of the present invention, the magnesium hydroxide was purchased from Hebei Xintao New Material Technology Co., Ltd., and the model is AHM-50 (particle size 1μm, purity ≥99%).

[0016] According to a preferred embodiment of the present invention, the toluene was purchased from Tianjin Kemei Chemical Reagent Co., Ltd., and the product name was toluene (analytical grade, CAS: 108-88-3).

[0017] According to a preferred embodiment of the present invention, the spherical boron nitride is purchased from Shanghai Changbei Nanomaterials Technology Co., Ltd., and is designated as "hexagonal boron nitride nanospheres".

[0018] According to a preferred embodiment of the present invention, in step A1, the reflux reaction time is 4-6 hours; the magnetic stirring reaction time is 6-8 hours.

[0019] According to a preferred embodiment of the present invention, in step A2, the ultrasonic treatment time is 2-4 hours; the solvothermal reaction time is 12-14 hours.

[0020] According to a preferred embodiment of the present invention, the preparation method of the epoxysiloxane-grafted ammonium polyphosphate includes: B1, adding ammonium polyphosphate to isopropanol, ultrasonically dispersing, adding γ-glycidoxypropyltrimethoxysilane, and refluxing at 70-72°C to generate an intermediate; B2, subsequently adding methyltrimethoxysilane and hydrochloric acid, stirring and hydrolyzing at 40-42°C, then heating to 80-82°C for condensation to generate organosilicon network-coated particles, filtering, washing with isopropanol, and vacuum drying at 80-82°C.

[0021] The preparation of epoxy-siloxane-grafted ammonium polyphosphate in this invention is completed in two steps. In the first step, the amino or hydroxyl groups on the surface of ammonium polyphosphate react with the epoxy group (-COC-) of γ-glycidoxypropyltrimethoxysilane under reflux conditions at 70-72°C. The epoxy group is attacked by the amino or hydroxyl group, and after ring opening, an intermediate containing Si-OP bonds is generated, allowing the siloxane segments to be chemically bonded to the surface of the ammonium polyphosphate particles, effectively improving its dispersibility. In the second step, methyltrimethoxysilane and hydrochloric acid are added. The hydrochloric acid catalyzes the hydrolysis of methyltrimethoxysilane to generate silanol containing Si-OH. At 40-42°C, the silanol further condenses with the siloxane hydroxyl groups on the surface of the intermediate, removing water molecules to form a Si-O-Si crosslinked network. The reaction is accelerated by heating to 80-82°C, and finally a three-dimensional organosilicon network is formed to coat the ammonium polyphosphate particles, which retains the flame retardant properties of ammonium polyphosphate while avoiding its agglomeration.

[0022] According to a preferred embodiment of the present invention, the ammonium polyphosphate was purchased from Jiangsu Tianteng Chemical Co., Ltd., and the model is TAP-100 (degree of polymerization n=100, total phosphorus content ≥30%).

[0023] According to a preferred embodiment of the present invention, the isopropanol was purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd., and the product name is isopropanol (analytical grade, CAS: 67-63-0).

[0024] According to a preferred embodiment of the present invention, the γ-glycidoxypropyltrimethoxysilane was purchased from Nanjing Shuguang Chemical Group Co., Ltd., and the product name is γ-glycidoxypropyltrimethoxysilane (KH560, purity ≥98%).

[0025] According to a preferred embodiment of the present invention, the methyltrimethoxysilane was purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd., and the product name is methyltrimethoxysilane (MTMS, purity ≥98%).

[0026] According to a preferred embodiment of the present invention, the hydrochloric acid was purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd., and the product was hydrochloric acid (analytical grade, concentration 36-38%, CAS: 7647-01-0).

[0027] According to a preferred embodiment of the present invention, in step B1, the ultrasonic dispersion time is 30-40 min; the reflux reaction time is 8-10 h.

[0028] According to a preferred embodiment of the present invention, in step B2, the stirring hydrolysis time is 2-4 hours; the condensation time is 4-6 hours; and the vacuum drying time is 10-15 hours.

[0029] This invention also provides a method for preparing the self-healing, high thermal conductivity silicon-based flame-retardant insulating adhesive film, comprising the following steps: S1. Organosilicon-modified borate ester containing dynamic disulfide bonds, epoxy siloxane-grafted ammonium polyphosphate, methyl vinyl silicone rubber, fumed silica, magnesium hydroxide, toluene, and spherical boron nitride are added to a planetary ball mill and dispersed using agate beads as the grinding medium to obtain a uniform slurry. S2. Pour the slurry into a polytetrafluoroethylene mold and dry it in an oven at 60-62℃. S3. Curing at 120-122℃.

[0030] The overall process of film preparation in this invention achieves functional integration through physical mixing and chemical crosslinking. In the first step, after mixing the raw materials (organosilicon-modified borate ester containing dynamic disulfide bonds, epoxysiloxane-grafted ammonium polyphosphate, methyl vinyl silicone rubber, etc.) with toluene, the agate beads of a planetary ball mill uniformly disperse the filler in the silicone rubber matrix through collision and shear force, avoiding agglomeration and ensuring interfacial bonding. In the second step, the slurry is poured into a mold and dried at 60-62℃. This removes the solvent toluene while promoting the initial stretching of the silicone rubber molecular chains and the formation of some weak interactions (such as hydrogen bonds), laying the foundation for subsequent curing. The third step involves curing at 120-122℃. The double bonds (-CH=CH2) of the methyl vinyl silicone rubber undergo an addition reaction with the hydrogen-containing silicone oil (a hidden component) in the system under platinum catalysis, forming a three-dimensional cross-linked network that fixes all components (boron ester modified particles, ammonium polyphosphate coated particles, fumed silica, spherical boron nitride, etc.) within it. The spherical boron nitride forms a through-type, rapid heat transfer, three-dimensional continuous thermal conductive network, ultimately endowing the film with comprehensive properties such as high thermal conductivity, self-healing, flame retardancy, and insulation.

[0031] According to a preferred embodiment of the present invention, in step S1, the dispersion time is 4-6 hours and the rotation speed is 300-400 rpm.

[0032] According to a preferred embodiment of the present invention, in step S2, the drying time in the oven is 24-26 hours.

[0033] According to a preferred embodiment of the present invention, in step S3, the curing time is 4-6 hours.

[0034] The beneficial effects of this invention are as follows: The self-healing, high thermal conductivity, flame-retardant, and insulating adhesive film of this invention achieves significant breakthroughs over traditional silicon-based materials in several key performance aspects through innovative component design and process optimization. Traditional silicon-based adhesive films suffer from weak interfacial bonding and poor filler dispersion, making it difficult to repair microcracks once they form, leading to shortened device lifespan. Simultaneously, their intrinsic thermal conductivity is low, failing to meet the heat dissipation requirements of high-power devices. In this invention, an organosilicon-modified borate ester containing dynamic disulfide bonds introduces low-dissociation-energy disulfide bonds, triggering bond breakage and recombination reactions at around 80°C. Combined with the flexible network support of the silicon substrate, the film can repair over 90% of microcracks after heating for 30 minutes following pre-existing cracks, significantly improving interfacial reliability.

[0035] The improved flame-retardant performance is another core advantage of this invention. Traditional silicon-based thin films mostly rely on halogens or single phosphorus-based flame retardants. The former releases toxic gases upon combustion, while the latter is prone to migration and loss, making it difficult to meet long-term safety requirements. In this invention, organosilicon-modified borate esters containing dynamic disulfide bonds release boron-containing oxides through the decomposition of the borate ester bonds, forming a dense barrier layer on the material surface to block oxygen diffusion; epoxy-siloxane-grafted ammonium polyphosphate forms a dual flame-retardant mechanism through the high-temperature dehydration and char formation of ammonium polyphosphate and gas-phase dilution.

[0036] The optimized overall performance of this invention makes the thin film uniquely valuable in scenarios such as electronic device packaging. The intrinsic low dielectric constant of the silicon substrate and the ion-free residue treatment on the modified compound surface ensure the insulating properties of the film, meeting the insulation requirements of precision electronic components. The synergistic effect of magnesium hydroxide and ammonium polyphosphate reduces smoke density and minimizes the release of harmful substances during combustion. Furthermore, the rational use of toluene solvent and the optimization of the dispersion process make the film preparation process more environmentally friendly and improve batch stability. These synergistic improvements in performance not only extend the service life of electronic devices and reduce maintenance costs caused by thermal runaway or interface failure, but also provide a reliable material solution for the thermal management needs of fields such as 5G communications and new energy vehicles. Attached Figure Description

[0037] Figure 1 Flowchart for the preparation of a self-healing, high thermal conductivity, silicon-based flame-retardant insulating adhesive film. Detailed Implementation

[0038] The present application will now be described in further detail with reference to the accompanying drawings. It should be noted that the following specific embodiments are only used to further illustrate the present application and should not be construed as limiting the scope of protection of the present application. Those skilled in the art can make some non-essential improvements and adjustments to the present application based on the above application content.

[0039] I. Implementation Examples Example 1 Preparation of organosilicon-modified borate esters containing dynamic disulfide bonds: 10 g of boric acid was added to 100 mL of anhydrous ethanol and refluxed at 78 °C for 5 h. After removing the ethanol by vacuum distillation, triethyl borate was obtained. 5 g of bis(triethoxysilyl) disulfide (a siloxane containing disulfide bonds) was added to the ester, and the mixture was heated to 81 °C and magnetically stirred for 7 h (300 rpm) to generate an intermediate. Subsequently, 5 g of boron nitride nanosheets were dispersed in 100 mL of N,N-dimethylformamide and sonicated for 3 h (40 kHz). After adding the intermediate, the mixture was heated to 121 °C and solvothermal reacted for 13 h (0.5 MPa). After cooling to room temperature, the mixture was filtered, washed three times alternately with N,N-dimethylformamide and ethanol, and dried under vacuum at 61 °C for 12 h to obtain organosilicon-modified borate esters containing dynamic disulfide bonds.

[0040] Preparation of epoxysiloxane-grafted ammonium polyphosphate: 5g of ammonium polyphosphate was added to 50mL of isopropanol and ultrasonically dispersed for 35min (frequency 40kHz). 3g of γ-glycidoxypropyltrimethoxysilane was added, and the mixture was heated to 71℃ and refluxed for 9h (using a reflux condenser). Subsequently, 2g of methyltrimethoxysilane and 1mL of hydrochloric acid (concentration 36%) were added, and the mixture was stirred and hydrolyzed at 41℃ for 3h (magnetic stirring, speed 200rpm). The mixture was then heated to 81℃ for condensation for 5h (using an oil bath). After the reaction was completed, the mixture was filtered, washed twice with isopropanol, and vacuum dried at 81℃ for 12h to obtain epoxysiloxane-grafted ammonium polyphosphate.

[0041] Preparation of self-healing high thermal conductivity silicon-based flame-retardant insulating adhesive film: 15g of the organosilicon modified borate ester containing dynamic disulfide bonds prepared above, 10g of epoxy siloxane-grafted ammonium polyphosphate, 100g of methyl vinyl silicone rubber, 25g of fumed silica, 12g of magnesium hydroxide, 65g of toluene, and 50g of spherical boron nitride were added to a planetary ball mill (30% agate bead filling) and dispersed at 350rpm for 5h; the dispersed slurry was poured into a 50mm×50mm×5mm polytetrafluoroethylene mold and dried in a 61℃ oven for 25h; after removal, it was cured at 121℃ for 5h to obtain a self-healing high thermal conductivity silicon-based flame-retardant insulating adhesive film.

[0042] Example 2 The specific implementation method is the same as in Example 1, except that the preparation of organosilicon-modified borate ester containing dynamic disulfide bonds is as follows: 10g of boric acid is added to 100mL of anhydrous ethanol and refluxed at 80℃ for 4h. After vacuum distillation, 5g of bis(triethoxysilyl) disulfide is added and magnetically stirred at 82℃ for 6h (350rpm). Subsequently, boron nitride nanosheets (5g) are dispersed in 100mL of N,N-dimethylformamide and ultrasonically treated for 2h (frequency 40kHz). After adding the intermediate, the reaction is solvothermal at 122℃ for 12h. After cooling and filtration, the mixture is washed with N,N-dimethylformamide and ethanol and vacuum dried at 62℃ for 11h.

[0043] Preparation of epoxysiloxane-grafted ammonium polyphosphate: 5g of ammonium polyphosphate was added to 50mL of isopropanol and ultrasonically dispersed for 30min (frequency 40kHz). 3g of γ-glycidoxypropyltrimethoxysilane was added and refluxed at 72℃ for 8h. Subsequently, 2g of methyltrimethoxysilane and 1mL of hydrochloric acid were added and hydrolyzed at 42℃ for 2h, followed by condensation at 82℃ for 4h. After filtration, the mixture was washed with isopropanol and vacuum dried at 82℃ for 10h.

[0044] Preparation of self-healing high thermal conductivity silicon-based flame-retardant insulating adhesive film: 15g of organosilicon modified borate ester containing dynamic disulfide bonds, 10g of epoxy siloxane-grafted ammonium polyphosphate, 100g of methyl vinyl silicone rubber, 25g of fumed silica, 12g of magnesium hydroxide, 65g of toluene, and 60g of spherical boron nitride were added to a planetary ball mill and dispersed at 300rpm for 6h; the slurry was poured into a mold and dried at 62℃ for 26h, and cured at 122℃ for 4h.

[0045] Example 3 The specific implementation method is the same as in Example 1, except that the preparation of organosilicon-modified borate ester containing dynamic disulfide bonds is as follows: 10g of boric acid is added to 100mL of anhydrous ethanol and refluxed at 79℃ for 6h. After vacuum distillation, 5g of bis(triethoxysilyl) disulfide is added and magnetically stirred at 81℃ for 8h (250rpm). Subsequently, boron nitride nanosheets (5g) are dispersed in 100mL of N,N-dimethylformamide and ultrasonically treated for 4h (frequency 40kHz). After adding the intermediate, the reaction is solvothermal at 121℃ for 14h. After cooling and filtration, the mixture is washed with N,N-dimethylformamide and ethanol and vacuum dried at 60℃ for 13h.

[0046] Preparation of epoxysiloxane-grafted ammonium polyphosphate: 5g of ammonium polyphosphate was added to 50mL of isopropanol and ultrasonically dispersed for 40min (frequency 40kHz). 3g of γ-glycidoxypropyltrimethoxysilane was added and refluxed at 70℃ for 10h. Subsequently, 2g of methyltrimethoxysilane and 1mL of hydrochloric acid were added and hydrolyzed at 40℃ for 4h, followed by condensation at 80℃ for 6h. After filtration, the mixture was washed with isopropanol and vacuum dried at 80℃ for 15h.

[0047] Preparation of self-healing high thermal conductivity silicon-based flame-retardant insulating adhesive film: 15g of organosilicon modified borate ester containing dynamic disulfide bonds, 10g of epoxy siloxane-grafted ammonium polyphosphate, 100g of methyl vinyl silicone rubber, 25g of fumed silica, 12g of magnesium hydroxide, 65g of toluene, and 40g of spherical boron nitride were added to a planetary ball mill and dispersed at 400rpm for 4h; the slurry was poured into a mold and dried at 60℃ for 24h, and cured at 120℃ for 6h.

[0048] Comparative Example 1 The specific implementation method is the same as in Example 1, except that the preparation of the self-healing high thermal conductivity silicon-based flame-retardant insulating adhesive film is as follows: 10g of epoxy siloxane-grafted ammonium polyphosphate (organosilicon modified borate ester without dynamic disulfide bonds) is added to a planetary ball mill along with 100g of methyl vinyl silicone rubber, 25g of fumed silica, 12g of magnesium hydroxide, 65g of toluene, and 50g of spherical boron nitride, and dispersed at 350rpm for 5h; after the slurry is poured into a mold, it is dried at 61℃ for 25h and cured at 121℃ for 5h.

[0049] Comparative Example 2 The specific implementation method is the same as in Example 1, except that the preparation of the self-healing high thermal conductivity silicon-based flame-retardant insulating adhesive film is as follows: 15g of organosilicon modified borate ester (epoxysiloxane-grafted ammonium polyphosphate without epoxy groups) containing dynamic disulfide bonds, 100g of methyl vinyl silicone rubber, 25g of fumed silica, 12g of magnesium hydroxide, 65g of toluene, and 50g of spherical boron nitride are added to a planetary ball mill and dispersed at 350rpm for 5h; after the slurry is poured into a mold, it is dried at 61℃ for 25h and cured at 121℃ for 5h.

[0050] Comparative Example 3 The specific implementation method is the same as in Example 1, except that the preparation of the self-healing high thermal conductivity silicon-based flame-retardant insulating adhesive film is as follows: 100g of methyl vinyl silicone rubber, 25g of fumed silica, 12g of magnesium hydroxide, 65g of toluene, and 50g of spherical boron nitride (epoxysiloxane-grafted ammonium polyphosphate and organosilicon-modified borate containing dynamic disulfide bonds) are added to a planetary ball mill and dispersed at 350rpm for 5h; after the slurry is poured into a mold, it is dried at 61℃ for 25h and cured at 121℃ for 5h.

[0051] Performance testing The composite materials prepared in each example and comparative example were tested according to the following steps: 1. Self-healing performance test: Take a 50mm×50mm×0.2mm film sample and make a straight scratch with a depth of about 100μm and a length of 50mm on its surface with a scalpel. Record the initial length of the scratch (L0) using an optical microscope (100x magnification). Place the sample in a 60℃ constant temperature oven for 24 hours. After removing it, measure the length of the healed scratch (L1) again using an optical microscope. Calculate the healing rate: (L0-L1) / L0×100%.

[0052] 2. Thermal conductivity test: A laser flash thermal conductivity meter (test temperature range 25-100℃) was used. The thin film sample (thickness 0.2mm, area 30mm×30mm) was fixed on the test platform, and thermal grease was evenly applied to both sides of the sample to ensure thermal contact. The test was performed 3 times at each temperature point and the average value was taken. The thermal conductivity was calculated by the thermal diffusivity (α) (λ=α×density×specific heat capacity), where the density and specific heat capacity were pre-determined by a densitometer and a differential scanning calorimeter.

[0053] 3. Flame retardant performance test: According to the UL94 vertical burning test standard, the film sample (size 125mm×13mm×0.2mm) is vertically fixed in the combustion test chamber. The lower end of the sample is ignited with a Bunsen burner flame (height 20mm, heat power 500W). The first ignition time (t1), the second ignition time (t2) and whether there are drips igniting cotton are recorded. Rating according to the UL94 standard (V-0, V-1, V-2, HB).

[0054] 4. Insulation performance test: Volume resistivity: Using a high resistance meter (test voltage 100V), after cleaning the sample surface with alcohol, clamp it between two circular electrodes (50mm in diameter, 2mm apart), and read the resistance value (R) after stabilizing for 1 minute. Volume resistivity (ρᵥ) = R×A / d (A is the electrode area, d is the sample thickness).

[0055] Breakdown field strength: The step voltage increase method is used. The sample is placed between two parallel metal plates (1 mm apart) and the voltage is increased at a rate of 1 kV / s until breakdown. The breakdown voltage (Vᵦ) is recorded and the breakdown field strength (Eᵦ) = Vᵦ / d.

[0056] 5. Mechanical strength test: Prepare dumbbell-shaped specimens (gauge length 20 mm, width 4 mm, thickness 0.2 mm) according to GB / T 1040-2006 standard. Use a universal testing machine (tensile rate 50 mm / min) to test the tensile strength (σ) and elongation at break (ε). Each specimen is tested 5 times and the average value is taken.

[0057] 6. Test Results: Table 1: Test results of each embodiment and comparative example Group Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Self-healing rate (%) 89 92 95 65 72 50 Thermal conductivity at 25℃ (W / (m·K)) 5.85 5.88 5.90 2.95 2.72 2.55 Thermal conductivity at 50℃ (W / (m·K)) 6.20 6.25 6.28 4.95 4.05 3.80 UL94 flame retardant rating V-0 V-0 V-0 V-1 V-1 HB Volume resistivity (Ω·cm) <![CDATA[1.2×10 13 ]]> <![CDATA[1.1×10 13 ]]> <![CDATA[1.0×10 13 ]]> <![CDATA[8.5×10 12 ]]> <![CDATA[9.8×10 12 ]]> <![CDATA[6.2×10 12 ]]> Breakdown field strength (MV / m) 35 36 37 28 30 25 Tensile strength (MPa) 4.2 4.5 4.8 3.2 3.5 2.8 Elongation at break (%) 12 13 14 8 9 6 As shown in Table 1, Examples 1-3 effectively solved the problems of low thermal conductivity, insufficient flame retardancy, and lack of self-healing ability of existing silicon-based adhesive films through the synergistic effect of organosilicon-modified borate esters containing dynamic disulfide bonds and epoxy-based siloxane-grafted ammonium polyphosphate. Performance test results show that the thermal conductivity of Examples 1-3 at 25℃ (5.85-5.90 W / (m·K)) and at 50℃ (6.20-6.28 W / (m·K)) is significantly higher than that of the comparative examples (2.55-2.95 W / (m·K) and 3.8-4.95 W / (m·K) for Comparative Examples 1-3, respectively). W / (m·K) indicates that the modifier improves thermal conductivity by optimizing molecular chain arrangement or forming a thermally conductive network; the UL94 flame retardant rating is V-0 for all examples (V-1 or HB for Comparative Examples 1-3), which is due to the endothermic decomposition of ammonium polyphosphate and the synergistic flame retardant effect of borate ester, effectively inhibiting flame propagation; the self-healing rate is as high as 89-95% (50-72% for Comparative Examples 1-3), thanks to the breaking-recombination characteristics of disulfide bonds in organosilicon-modified borate ester containing dynamic disulfide bonds during heating, which allows the molecular chains at the scratch to re-crosslink and repair, while the epoxy-siloxane grafted with ammonium polyphosphate provides additional crosslinking points to enhance the healing ability. In addition, the volume resistivity of Examples 1-3 (1.0×10⁻⁶ m·K) is significantly lower than that of Comparative Examples 1-3. 13 -1.2×10 13The breakdown field strength (35-37 MV / m) is superior to the comparative example, and the tensile strength (4.2-4.8 MPa) and elongation at break (12-14%) meet the packaging requirements of electronic components. Its overall performance is significantly better than the comparative example, which suffers from poor thermal conductivity, weak flame retardancy, and difficulty in self-healing due to the lack of modifiers. It meets the thermal management and safety requirements of high-power equipment.

[0058] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.

Claims

1. A self-healing, high thermal conductivity, silicon-based flame-retardant insulating adhesive film, characterized in that, The ingredients include the following parts by weight: Methyl vinyl silicone rubber: 90-110 parts by weight; Organosilicon-modified borate ester containing dynamic disulfide bonds: 10-20 parts by weight; Epoxysiloxane-grafted ammonium polyphosphate: 5-15 parts by weight; Fumed silica: 20-30 parts by weight; Magnesium hydroxide: 10-15 parts by weight; Toluene: 50-80 parts by weight; Spherical boron nitride: 40-60 parts by weight; The preparation steps of the organosilicon-modified borate ester containing dynamic disulfide bonds include: A1, adding boric acid to anhydrous ethanol, refluxing to generate triethyl borate, distilling under reduced pressure, adding a siloxane containing disulfide bonds, and reacting with magnetic stirring at 80-82℃ to generate an intermediate; A2, subsequently, dispersing boron nitride nanosheets in N,N-dimethylformamide, sonicating, adding the intermediate, and reacting with a solvothermal agent at 120-122℃, filtering after cooling, washing alternately with N,N-dimethylformamide and ethanol, and vacuum drying at 60-62℃.

2. The self-healing, high thermal conductivity silicon-based flame-retardant insulating adhesive film according to claim 1, characterized in that, In step A1, the reflux reaction time is 4-6 hours; the magnetic stirring reaction time is 6-8 hours.

3. The self-healing, high thermal conductivity silicon-based flame-retardant insulating adhesive film according to claim 1, characterized in that, In step A2, the ultrasonic treatment time is 2-4 hours; the solvothermal reaction time is 12-14 hours.

4. The self-healing, high thermal conductivity silicon-based flame-retardant insulating adhesive film according to claim 1, characterized in that, The preparation method of the epoxysiloxane-grafted ammonium polyphosphate includes: B1, adding ammonium polyphosphate to isopropanol, ultrasonically dispersing, adding γ-glycidoxypropyltrimethoxysilane, and refluxing at 70-72°C to generate an intermediate; B2, subsequently adding methyltrimethoxysilane and hydrochloric acid, stirring and hydrolyzing at 40-42°C, then heating to 80-82°C for condensation to generate organosilicon network-coated particles, filtering, washing with isopropanol, and vacuum drying at 80-82°C.

5. The self-healing, high thermal conductivity silicon-based flame-retardant insulating adhesive film according to claim 4, characterized in that, In step B1, the ultrasonic dispersion time is 30-40 min; the reflux reaction time is 8-10 h.

6. The self-healing, high thermal conductivity silicon-based flame-retardant insulating adhesive film according to claim 4, characterized in that, In step B2, the stirring hydrolysis time is 2-4 hours; the condensation time is 4-6 hours; and the vacuum drying time is 10-15 hours.

7. A method for preparing a self-healing, high thermal conductivity silicon-based flame-retardant insulating adhesive film according to any one of claims 1-6, characterized in that, step include: S1. Organosilicon-modified borate ester containing dynamic disulfide bonds, epoxy siloxane-grafted ammonium polyphosphate, methyl vinyl silicone rubber, fumed silica, magnesium hydroxide, toluene, and spherical boron nitride are added to a planetary ball mill and dispersed using agate beads as the grinding medium to obtain a uniform slurry. S2. Pour the slurry into a polytetrafluoroethylene mold and dry it in an oven at 60-62℃. S3. Curing at 120-122℃.

8. The preparation method according to claim 7, characterized in that, In step S1, the dispersion time is 4-6 hours and the rotation speed is 300-400 rpm.

9. The preparation method according to claim 7, characterized in that, In step S2, the drying time in the oven is 24-26 hours.

10. The preparation method according to claim 7, characterized in that, In step S3, the curing time is 4-6 hours.